2019
DOI: 10.1088/1748-9326/ab4928
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional unfairness when applying new greenhouse gas emissions metrics at country level

Abstract: The 2015 Paris Agreement sets out that rapid reductions in greenhouse gas (GHG) emissions are needed to keep global warming to safe levels. A new approach (known as GWP * ) has been suggested to compare contributions of long-and short-lived GHGs, providing a close link between cumulative CO 2 -equivalent emissions and total warming. However, comparison factors for non-CO 2 GHGs under the GWP * metric depend on past emissions, and hence raise questions of equity and fairness when applied at any but the global l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 22 publications
1
46
0
Order By: Relevance
“…There continues to be a vigorous debate about the applicability of different emission metrics (e.g., Myhre et al, 2013); metric choice depends on the particular policy context in which they are applied, and the degree to which continuity of choice is important in that context (e.g., Allen et al, 2018; Cain et al, 2019; Rogelj & Schleussner, 2019). A specific development has been the suggested use of metrics that compare one‐off pulse emissions of long‐lived gases (such as CO 2 ) with step‐changes in emissions of short‐lived species (e.g., gases with lifetimes less than a few decades), on the basis that this leads to a more informed comparison of their ultimate impact on temperature; such approaches can either adopt GWP values, but adapt their usage (Allen et al, 2016) or more directly compute the pulse‐step equivalence (W. J. Collins et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…There continues to be a vigorous debate about the applicability of different emission metrics (e.g., Myhre et al, 2013); metric choice depends on the particular policy context in which they are applied, and the degree to which continuity of choice is important in that context (e.g., Allen et al, 2018; Cain et al, 2019; Rogelj & Schleussner, 2019). A specific development has been the suggested use of metrics that compare one‐off pulse emissions of long‐lived gases (such as CO 2 ) with step‐changes in emissions of short‐lived species (e.g., gases with lifetimes less than a few decades), on the basis that this leads to a more informed comparison of their ultimate impact on temperature; such approaches can either adopt GWP values, but adapt their usage (Allen et al, 2016) or more directly compute the pulse‐step equivalence (W. J. Collins et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, we have shown that applying GWP * directly to the Paris Agreement would introduce major conflicts in the Agreement's architecture, undermine its overall internal consistency and deteriorate the environmental integrity of the targets that are set out in the Agreement's Articles 2 and 4. As a result of its dependency on historic emissions, applying GWP * to any other than the global level further raises fundamental questions of fairness and equity (Rogelj and Schleussner 2019). With the explicit reference to equity in Article 4 and given the national determined nature of the Paris Agreement, this further limits the scope of the applicability of the metric in climate policy.…”
Section: Discussionmentioning
confidence: 99%
“…Noted that the grandfathering approach determines the national efforts relying on the current emissions and is not conducive to countries with relatively low emissions in the base year. Thus, it is often criticized in the literature 35,36 . However, we choose to include it in the average because it represents one of the five IPCC equity categories and is implicitly followed by many of the developed countries 8,37 .…”
Section: Methodsmentioning
confidence: 99%